Retrocaval ureter and right ureteropelvic junction obstruction: a case report and literature review - Jiang, Ze-Sheng; Yan, Min-Bo; Lv, Zhuan; He, Ji-Rong; Wen, Wei-Jun; Mai, Chuan-Xin; Tu, Fa-Rong; Li, Jian-Sheng (Frontiers in Medicine, 2025)
A clinical case involving a patient with retrocaval ureter and right ureteropelvic junction obstruction (UPJO) is presented, accompanied by a comprehensive review and discussion of relevant literature. The patient, a 43-year-old female, was admitted to the hospital after discovering right hydronephrosis 2 weeks prior. Computed tomographic urography (CTU) revealed significant right hydronephrosis, a retrocaval ureter, and compression of the right renal variant artery causing UPJO. Retrograde pyelography further demonstrated a stenotic upper segment of the right ureter, exhibiting an “S”-shaped appearance. To address these issues, the patient underwent laparoscopic surgery for retrocaval ureteral realignment and right pyeloureteroplasty. Notably, there were no complications during or after the surgical procedure, and the patient’s recovery was uneventful. The coexistence of retrocaval ureter and right UPJO is infrequently encountered in clinical practice. However, the simultaneous correction of these anomalies through laparoscopic surgery has proven to be both safe and feasible.